The Politics of Inclusive Development: Interrogating the Evidence - Hickey, Sam; Bukenya, Badru; Sen, Kunal (Oxford University Press, 2014)
It is now widely accepted that politics plays a significant role in shaping the possibilities for inclusive development. However, the specific ways in which this happens across different types and forms of development, and in different contexts, remains poorly understood. This collection provides the state of the art review regarding what is currently known about the politics of inclusive development. Leading academics offer systematic reviews of how politics shapes development across multiple dimensions, including through growth, natural resource governance, poverty reduction, service delivery, social protection, justice systems, the empowerment of marginalized groups, and the role of both traditional and non-traditional donors. The book not only provides a comprehensive update but also a groundbreaking range of new directions for thinking and acting around these issues. The book's originality thus derives not only from the wide scope of its case-study material, but also from the new conceptual approaches it offers for thinking about the politics of inclusive development, and the innovative and practical suggestions for donors, policymakers, and practitioners that flow from this.